2013
DOI: 10.1088/1748-0221/8/01/c01046
|View full text |Cite
|
Sign up to set email alerts
|

Improving the spatial resolution of soft X-ray detection using an Electron-Multiplying Charge-Coupled Device

Abstract: The Super Advanced X-ray Emission Spectrometer (SAXES) is an instrument at the Swiss Light Source designed for Resonant Inelastic X-ray Scattering with an energy resolution (E/∆E) better than 12000 at 930 eV. Improvements to the instrument have been predicted that could allow the energy resolution to be improved by a factor of two. To achieve this, the spatial resolution of the detector (currently a Charge-Coupled Device, CCD) over which the energy spectrum is dispersed would have to be improved to better than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 7 publications
0
16
0
Order By: Relevance
“…In the field of synchrotron research it has been demonstrated that the EM-CCD can bring many benefits to spatially dispersive soft X-ray spectrometers [24][25][26][27][28] . The ability to operate the spectrometer in photon-counting mode due to the high-speed readout with sub-electron readout noise allows centroiding techniques to be used.…”
Section: Direct Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the field of synchrotron research it has been demonstrated that the EM-CCD can bring many benefits to spatially dispersive soft X-ray spectrometers [24][25][26][27][28] . The ability to operate the spectrometer in photon-counting mode due to the high-speed readout with sub-electron readout noise allows centroiding techniques to be used.…”
Section: Direct Detectionmentioning
confidence: 99%
“…The ability to operate the spectrometer in photon-counting mode due to the high-speed readout with sub-electron readout noise allows centroiding techniques to be used. The use of photoncounting and centroiding allows order of magnitude improvements to be made to the spatial resolution, impacting directly on the spectral resolution achievable with the spectrometer [24][25][26][27][28] , both in ground-based applications and in space 29 .…”
Section: Direct Detectionmentioning
confidence: 99%
“…Similar experiments were repeated with the CCD97 20 , a standard back-illuminated EM-CCD from e2v technologies with 16 µm pixels, across four energies: 530 eV, 680 eV, 850 eV and 1000 eV 21,22 . With the EM-CCD, it is possible to reduce the readout noise to the sub-electron level through increasing the gain, albeit with an increase in the noise on the signal levels themselves from the associated Modified Fano Factor (Section 5).…”
Section: Em-ccd Camera Development For Saxesmentioning
confidence: 99%
“…Measurements of centroiding 850 eV and 1000 eV X-ray events detected with an EM-CCD has demonstrated achievable spatial resolutions better than 2.2 μm (FWHM) when averaged across the pixel's geometric area [7]. Due to the experimental setup, the measurement includes an unknown contribution from the X-ray source's size.…”
Section: Introductionmentioning
confidence: 99%